Structural Divergence in Reproductive Agency: Unraveling the 'Matrilineal Buffer' Against Contraceptive Discontinuation in Indonesia Using Multi-Group SEM - Leonardo Simanjuntak; Cinthya Callathea; Desiree Montesinos; Firzan Dahlan (HM Publisher, 2025)
Despite the historical success of Indonesia's family planning program, the contraceptive prevalence rate (CPR) has stagnated, driven largely by high rates of contraceptive discontinuation (29%). Conventional demographic analyses often attribute this to biomedical side effects, overlooking the structural influence of kinship systems and the potential confounding role of socioeconomic status. This study aims to analyze the structural pathways linking patriarchal gender norms to contraceptive discontinuation, mediated by reproductive autonomy, while explicitly controlling for educational attainment. We compare Indonesia’s two dominant cultural groups: the matrilineal Minangkabau and the patriarchal Javanese. A comparative cross-sectional study was conducted with 1,450 married women of reproductive age in West Sumatra (Minangkabau, n=725) and Central Java (Javanese, n=725). We employed Multi-Group Structural Equation Modeling (MG-SEM) with a rigorous invariance testing protocol. The model tested the